Pengembangan Model Pembelajaran melalui e-Learning - Pujiyanto Pujiyanto; Mahmuddin Yunus (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2004)
e-Learning, a learning model through internet, can be categorized as distance education. e-Learning involves education management, information technology (i.e., internet), and education technology. Such a learning model helps lecturers, teachers, college students, and other education practitioners improve the quality of the teaching learning process, especially through the establishment of communication network, correspondence, and discussion groups. It can also build linkages with other web-based learning resources in education-related as well as other fields.